Pengembangan Buku Literasi Kimia Kearifan Lokal Budaya Madura Berbasis Augmented Reality (AR) - Dwiarini Yuendita; Dina Dina (Jurnal Penelitian Pendidikan IPA, 2024)
This study provides a detailed description of the development of a chemical literacy book on Madurese local cultural wisdom based on augmented reality (AR). The research aims to identify the characteristics of chemical literacy books, then evaluate their suitability based on teacher usability tests and student readability tests. This research used an exploratory mixed methods design. The instruments used were a needs analysis questionnaire, expert validation sheet chemistry learning, teacher usability questionnaire sheet, and student readability questionnaire sheet. Feasibility assessments include content and scientific literacy, language, presentation, graphics, usefulness and attractiveness. The output of this research is a chemical literacy book on Madurese local cultural wisdom based on Augmented Reality (AR) in printed form consisting of 7 (seven) cultural themes and 7 (seven) Basic Competencies in the 2013 Curriculum referring to the Minister of Education and Culture Regulation and Culture Regulation Number 37 of 2018. The book This was declared suitable for use as a learning resource based on chemistry teachers' usability test responses with Very Good (SB) criteria in all aspects with an ideal percentage of 91.50% and based on student readability test responses with Very Good (SB) criteria in all aspects with an ideal percentage amounting to 87.91%.